Inhibition of Skp1-Cullin-F-box complexes during bovine oocyte maturation and preimplantation development leads to delayed development of embryos†. Issue 4 (7th December 2018) - Kinterova, Veronika; Kanka, Jiri; Petruskova, Veronika; Toralova, Tereza
Abstract: The mechanism of maternal protein degradation during preimplantation development has not been clarified yet. It is thought that a lot of maternal proteins are degraded by the ubiquitin–proteasome system. In this study, we focused on the role of the SCF (Skp1-Cullin-F-box) complexes during early bovine embryogenesis. We inhibited them using MLN4924, an inhibitor of SCF complex ligases controlled by neddylation. Oocytes maturated in MLN4924 could be fertilized, but we found no cumulus cell expansion and a high number of polyspermy after in vitro fertilization. We also found a statistically significant deterioration of development after MLN4924 treatment. After treatment with MLN4924 from the four-cell to late eight-cell stage, we found a statistically significant delay in their development; some of the treated embryos were, however, able to reach the blastocyst stage later. We found reduced levels of mRNA of EGA markers PAPOLA and U2AF1A, which can be related to this developmental delay. The cultivation with MLN4924 caused a significant increase in protein levels in MLN4924-treated oocytes and embryos; no such change was found in cumulus cells. To detect the proteins affected by MLN4924 treatment, we performed a Western blot analysis of selected proteins (SMAD4, ribosomal protein S6, centromeric protein E, P27, NFKB inhibitor alpha, RNA-binding motif protein 19). No statistically significant increase in protein levels was detected in either treated embryos or oocytes. In summary, our study shows that SCF ligases are necessary for the correct maturation of oocytes, cumulus cell expansion, fertilization, and early preimplantation development of cattle. Abstract : SCF complexes are involved in normal oocyte maturation, polysperm defense, and correct course of preimplantation development.